2020
DOI: 10.1021/acs.langmuir.9b03561
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Behavior of Complex Coacervates with Internal Lipid Vesicles under Nonequilibrium Conditions

Abstract: During the evolution of life on earth, the emergence of lipid membrane-bounded compartments is one of the most enigmatic events. Endosymbiosis has been hypothesized as one of the solutions. In this work, using a coacervate droplet formed by single-stranded oligonucleotides (ss-oligo) and poly(L-lysine) (PLL) as the protocell model, we monitored the uptake of liposomes of different types and studied the dynamic behavior of the resulting composite droplet under the electric field. The coacervate droplet exhibits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…The simplicity and biological relevance of such droplets have made them systems of interest as models for protocells and biomolecular condensates[ 77 , 86 ]. The charge ratio of the coacervate (that is, the ratio of polycation to polyanion) impacts its physical properties: Coacervates with a high ratio (more polycation) have a more positive zeta potential[ 87 , 88 ]. Vesicles have assembled at the surface of complex coacervates, much the same as in some ATPSs ( Fig.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The simplicity and biological relevance of such droplets have made them systems of interest as models for protocells and biomolecular condensates[ 77 , 86 ]. The charge ratio of the coacervate (that is, the ratio of polycation to polyanion) impacts its physical properties: Coacervates with a high ratio (more polycation) have a more positive zeta potential[ 87 , 88 ]. Vesicles have assembled at the surface of complex coacervates, much the same as in some ATPSs ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Vesicle localization in relation to complex coacervates is dependent on several factors. A recent study indicates that vesicles have a general tendency to diffuse into a complex coacervate, as their component molecules generally contain positive, negative, and hydrophobic sections[ 88 ]. That study found that negatively-charged vesicles primarily remained at coacervate surfaces with a net positive charge, but the same did not hold for positively-charged vesicles and negatively-charged coacervate surfaces ( Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Certain LLPS systems can also interact with, scaffold, and/or segregate lipid vesicles, perhaps foreshadowing a transition from membraneless compartments to membrane-bound compartments at some point at the origins of life (Tang et al 2014;Jia et al 2014Jia et al , 2019Jing et al 2019;Pir Cakmak et al 2019;Lin et al 2020). Other prebiotically relevant functions observed in phase-separated droplets include division (Yin et al 2016;Zwicker et al 2016), fusion (Jing et al 2020), and protection of encapsulated molecules from degradation (Okihana and Ponnamperuma 1982; Zhao and Zacharia 2018), all of which could assist in evolution of a primitive compartment. While functions in primitive LLPS systems appear to be relatively simple compared to modern engineering applications, there are cases where functions or properties of primitive LLPS can be used in applied technologies.…”
Section: Common Primitive Compartment Model Systemsmentioning
confidence: 99%